INFLUENCE OF CONSUMERS KNOWLEDGE TO SHADAQAH PAYING DECISION AT BAITUL MAAL UNISBA - Tresnati, Ratih; Sevriana, Lufthia; Hasanah, Eneng Nur (Universitas Islam Negeri Raden Intan Lampung, 2016)
Abstract- Shadaqah has a very important role to every human when we leave this world, therefore moslem community build a foundation to take care of their shadaqah from Muzaki. Unisba as an Islamic University, also have organization to collect, manage, and allocate funding from shadaqah, named Baitul Maal of Unisba. There are 419 lecturers and employees in Unisba but there are only 27% from them who decide to become muzzaki at Baitul Maal of Unisba. On average, the Collected Fund at Baitul Maal of Unisba per month is only as many as Rp 3.000.000,-. Researchers assumed that it caused by lack of consumers knowledge about Baitul Maal of Unisba programs. Consumers knowledge consists of attributes, benefit, and satisfaction to the products or services. A total of 30 questionnaires from offline surveys has been analysed using “several statistical analysis”, including multiple regression. Result of this research shows us that satisfaction to the products or services is the most dominant variable that influence lecturers and employees to become muzzzaki at Baitul Maal of Unisba.